2013
DOI: 10.1161/circulationaha.113.001545
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis in Adults With Bacterial Meningitis

Abstract: Background— Endocarditis may precede or complicate bacterial meningitis, but the incidence and impact of endocarditis in bacterial meningitis are unknown. Methods and Results— We assessed the incidence and clinical characteristics of patients with meningitis and endocarditis from a nationwide cohort study of adults with community-acquired bacterial meningitis in the Netherlands from 2006 to 2012. Endocarditis was identified in 24 of 1025 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 24 publications
(28 reference statements)
2
52
0
3
Order By: Relevance
“…These scattered reports and our results both demonstrated that meningitis is a rare neurological complication but is associated with a high probability of an unfavorable outcome 30 . The reason may be destructive neurological dysfunction by diffused brain infection 30 . The result of brain abscess has not been reported previously.…”
Section: Outcome and Impact Of Neurosurgery After Neurological Complisupporting
confidence: 65%
See 3 more Smart Citations
“…These scattered reports and our results both demonstrated that meningitis is a rare neurological complication but is associated with a high probability of an unfavorable outcome 30 . The reason may be destructive neurological dysfunction by diffused brain infection 30 . The result of brain abscess has not been reported previously.…”
Section: Outcome and Impact Of Neurosurgery After Neurological Complisupporting
confidence: 65%
“…In the limited reports, the incidence of a brain abscess may range from 2.8% to 30% based on the different diagnostic tools and criteria 29 . Endocarditis is an uncommon condition in bacterial meningitis, identified in 2% 30 of patients and 1.1% 29 complications of patients with IE. Our study revealed 0.7% cases of IE-related abscess and 0.5% cases of meningitis, confirmed by imaging.…”
Section: Discussion Neurological Complications Of Infective Endocardimentioning
confidence: 99%
See 2 more Smart Citations
“…Upper respiratory infection or soft tissue infection precede IE due to S. pyogenes 2. A nationwide cohort study in the Netherlands suggested that they found 24 cases (2%) of IE in 1025 patients with all bacterial meningitis and only one case was due to S. pyogenes although the detail was not described 12. From these epidemiological data, we assumed that IE was the primary cause of her clinical course in the present case, although we could not completely deny another hypothesis; IE might be secondary to bacterial meningitis.…”
Section: Discussionmentioning
confidence: 62%